Debating women : gender, education, and spaces for argument, 1835-1945 - Woods, Carly S. (Rhetoric and public affairs series., 2018)
"Spanning a historical period that begins with women's exclusion from university debates and continues through their participation in coeducational intercollegiate competitions, Debating Women highlights the crucial role that debating organizations played as women sought to access the fruits of higher education in the United States and United Kingdom. Despite various obstacles, women transformed forests, parlors, dining rooms, ocean liners, classrooms, auditoriums, and prisons into vibrant spaces for ritual argument. There, they not only learned to speak eloquently and argue persuasively but also used debate to establish a legacy, explore difference, engage in intercultural encounter, and articulate themselves as citizens. These debaters engaged with the issues of the day, often performing, questioning, and occasionally refining norms of gender, race, class, and nation. In tracing their involvement in an activity at the heart of civic culture, Woods demonstrates that debating women have much to teach us about the ongoing potential for debate to move arguments, ideas, and people to new spaces"--Publisher's description.